Exploring pregnancy and postpartum experiences among geographically diverse elite athletes: a qualitative study - McGregor, B.; McGrath, R.; Young, J.; Nottle, C. (Journal of Science and Medicine in Sport, 2024)
Objectives Female athletes who experience childbirth during their athletic careers can expect to return to elite sports postpartum and perform at a comparable or improved level. However, mothering athletes often encounter significant barriers when re-entering elite sports. The aim of this study was to explore the experiences of a geographically diverse group of mothering athletes who returned to elite sports after childbirth.